PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN PADA THEOBEROI BEACH RESORT BALI - Ni Kadek Ayu Diah Candra Dewi; Ni Nyoman Suryani; Ni Made Dwi Puspitawati (VALUES, 2023)
Rapid business development, especially in the tourism sector today, encourages companies or organizations to optimize their resources to face competition. This study aims to determine the effect of work discipline, work motivation, and work placement on employee performance at The Oberoi Beach Resort Bali. This research was conducted at The Oberoi Beach Resort Bali which is located at Seminyak Beach, Jl. Kayu Aya, Seminyak, Kuta, Bali. The objects of research at Oberoi Beach Resort Bali are work discipline (X1), work motivation (X2), work placement (X3) and employee performance (Y). The population in this study were all employees of The Oberoi Beach Resort Bali, totaling 60 employees. Sampling of this study using saturated sampling technique. Data collection methods used in this study are observation, documentation and questionnaires. The data analysis technique used in this study is multiple linear regression analysis. The results showed that work discipline, work motivation, and work placement have a positive and significant effect on employee performance at Oberoi Beach Resort Bali, this means that the more disciplined employees will improve performance.